2016
DOI: 10.1088/1741-2560/13/2/026010
|View full text |Cite
|
Sign up to set email alerts
|

Extracting duration information in a picture category decoding task using hidden Markov Models

Abstract: Objective Adapting classifiers for the purpose of brain signal decoding is a major challenge in brain–computer-interface (BCI) research. In a previous study we showed in principle that hidden Markov models (HMM) are a suitable alternative to the well-studied static classifiers. However, since we investigated a rather straightforward task, advantages from modeling of the signal could not be assessed. Approach Here, we investigate a more complex data set in order to find out to what extent HMMs, as a dynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…In previous studies we demonstrated beneficial properties of hidden Markov models (HMMs) in the context of BCI decoding [1,2]. So far, the majority of studies covering the use of HMMs for BCI decoding (including ours) have focused on offline (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…In previous studies we demonstrated beneficial properties of hidden Markov models (HMMs) in the context of BCI decoding [1,2]. So far, the majority of studies covering the use of HMMs for BCI decoding (including ours) have focused on offline (e.g.…”
Section: Introductionmentioning
confidence: 96%